2021
DOI: 10.1186/s41938-021-00477-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential of the entomopathogenic fungus, Metarhizium anisopliae s.l. in controlling live-wood eating termite, Microtermes obesi (Holmgren) (Blattodea: Termitidae) infesting tea crop

Abstract: Background In recent years, Microtermes obesi (Holmgren) (Blattodea: Termitidae) has been recorded as a major pest of tea crop, causes significant losses in production. Managing termite pests in tea crops through an integrated approach has been suggested, and the use of microbial biocontrol agent is one of the economical methods. The present study evaluated the pathogenic efficacy of an entomopathogenic fungus Metarhizium anisopliae s.l. (= M. anisopliae) against M. obesi damaging tea plants un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Entomopathogenic microbes are effective against the tea green leafhopper, Empoasca onukii Matsuda, the tea mosquito bug, Helopeltis theivora Water, the red spider mite, Oligonychus coffeae Nietner, among many others (Idris et al, 2020 ). In particular, beneficial fungi, including various Trichoderma species, and the entomopathogenic fungi Beauveria bassiana and Metarhizium anisopliae , have shown potential for control of tea mites and termites that attack tea, i.e., the live-wood eating termite, Microcerotermes beesoni Snyder, and other insect pests (Kumhar et al, 2020 ; Deka et al, 2021 ). However, infestation by the tea geometrid, Ectropis obliqua , remains difficult to control, with current pest management strategies broadly applying large doses of chemical pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…Entomopathogenic microbes are effective against the tea green leafhopper, Empoasca onukii Matsuda, the tea mosquito bug, Helopeltis theivora Water, the red spider mite, Oligonychus coffeae Nietner, among many others (Idris et al, 2020 ). In particular, beneficial fungi, including various Trichoderma species, and the entomopathogenic fungi Beauveria bassiana and Metarhizium anisopliae , have shown potential for control of tea mites and termites that attack tea, i.e., the live-wood eating termite, Microcerotermes beesoni Snyder, and other insect pests (Kumhar et al, 2020 ; Deka et al, 2021 ). However, infestation by the tea geometrid, Ectropis obliqua , remains difficult to control, with current pest management strategies broadly applying large doses of chemical pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…The results clearly signified the bioefficacy of Metarhizium against sugarcane termites and are in accordance with the reports of Kimberly and Seow (2017) who reported Metarhizium as potential biocontrol control agents against agricultural pests, termites and biological vectors. Deka et al (2021) inferred the potential of entomopathogenic fungi, M. anisopliae against termites infesting tea crop and found it to be effective in managing the pest, besides no phytotoxic effect on tea leaves, and with acceptable organoleptic attributes. Mishra et al (2021) in their review on biological approaches for termite management clearly indicated Metarhizium as microbial based antagonist and termitoxicant.…”
Section: Resultsmentioning
confidence: 99%
“…The application of entomopathogenic fungi in controlling pests has become a catchy topic for many researchers [133][134][135]. It is a gripping mechanism to evaluate how entomopathogenic fungi control insect pests.…”
Section: Protection Against Insect Pestsmentioning
confidence: 99%